2010
DOI: 10.1007/s12029-010-9200-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cancer Care for Hepatocellular Carcinoma at Two Tertiary-Care Referral Centers from High and Low Endemic Regions for Viral Hepatitis

Abstract: This study validates divergence in HCC presentation between low and high endemic regions for viral hepatitis. In addition, for the first time, differences in cancer care of HCC are documented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The largest Saudi study by Sanai et al conducted on 206 HCC patients in 2010 showed HCV preponderance in Saudi HCC patients ( 44 ). While, two other researches by Alsohaibani et al reaffirmed HCV predominance ( 43 ), the oldest study by Ayoola et al on 108 cases in 2004 ended up with a much higher rate of HBV infection (63.6%), compared to a tiny 8.5% of HCV. This showed a chronological disparity in the etiology of HCC in Saudi Arabia ( 45 ).…”
Section: Resultsmentioning
confidence: 92%
“…The largest Saudi study by Sanai et al conducted on 206 HCC patients in 2010 showed HCV preponderance in Saudi HCC patients ( 44 ). While, two other researches by Alsohaibani et al reaffirmed HCV predominance ( 43 ), the oldest study by Ayoola et al on 108 cases in 2004 ended up with a much higher rate of HBV infection (63.6%), compared to a tiny 8.5% of HCV. This showed a chronological disparity in the etiology of HCC in Saudi Arabia ( 45 ).…”
Section: Resultsmentioning
confidence: 92%
“…Many previous reports have confirmed the association between thrombocytopenia and HCC [27]. For example, it has been suggested that thrombocytopenia in a cirrhotic patient is more commonly associated with the development of HCC compared to non-thrombocytopenic, cirrhotic patients [18]- [20] [27]. Furthermore, patients with thrombocytopenia are more likely to have advanced hepatocellular carcinoma [28].…”
Section: Discussionmentioning
confidence: 89%
“…The causal distribution of HCC shows geographic variations. Thus, in Canadian patients, 45% of cases were attributable to alcohol-induced cirrhosis, 26% to cryptogenic cirrhosis and 13% to hepatitis C. In patients from Saudi Arabia, 47% of HCC were caused by hepatitis C, 27% by cryptogenic cirrhosis and 21% to hepatitis B [48]. In USA, regarding the HCC cause, 54.9% of cases were induced by HCV, 16.4% by alcohol, 14.1% by NAFLD and 9.5% by HBV [10].…”
Section: Nash-induced Hccmentioning
confidence: 99%